Production of biosurfactant from used cooking oil by local bacterial isolates for heavy metals removal - Md Badrul Hisham, Nurul Hanisah (2019)
Heavy metals from industrial effluents and sewage contribute to serious water pollution in most developing countries. The constant penetration and contamination of heavy metals into natural water sources may substantially raise the chances of human exposure to these metals through ingestion, inhalation or skin contact which could lead to liver damage, cancer and other severe conditions in the long term. Biosurfactant as an efficient biological surface active agent may provide an alternative solution for the removal of heavy metals from the industrial wastes. Biosurfactants exhibit the properties of reducing surface and interfacial tension, stabilizing emulsions, promoting foaming, high selectivity and specific activity at extreme temperatures, pH, and salinity, and ability to be synthesized from renewable resources. The ecofriendly and biodegradable nature of biosurfactants make their usage more favourable over chemical surfactants. Therefore, this study aimed to produce biosurfactant from renewable feedstock which is used cooking oil (UCO) by local isolates for heavy metals removal. Four bacterial isolates capable of utilizing UCO as a carbon source were isolated using Bushnell and Haas agar and screened for biosurfactant production with the help of oil spreading assay and surface tension activity. Out of the four Gram-positive isolates, the strain HIP3 showed the highest oil displacement area with the lowest surface tension of 38 mN/m after 7 days of culturing in mineral salt medium and 2% (v/v) UCO at temperature of 30°C and agitation of 200 rpm. Strain HIP3 was identified as Bacillus sp. based on 16S rRNA gene sequencing and was selected as a potential biosurfactant producing microorganism. Extraction method using chloroform: methanol (2:1) as the solvents gave the highest biosurfactant yield which is 9.5 g/L. High Performance Liquid Chromatography (HPLC) analysis confirmed that the biosurfactant produced by Bacillus sp. HIP3 consists of a lipopeptide similar to standard surfactin. The biosurfactant capable of removing 13.57%, 12.71%, 2.91%, 1.68%, and 0.7% of copper, lead, zinc, chromium, and cadmium, respectively from artificially contaminated water, highlighting its potential for bioremediation.